+0  
 
0
425
3
avatar

x^3+x^2+2x+2 factor by grouping so it ends up with two binomials.

Guest Dec 5, 2014

Best Answer 

 #2
avatar+20549 
+5

x^3+x^2+2x+2 factor by grouping so it ends up with two binomials.

$$\small{
\text{Formula:}
$
\boxed{a+ax+x^2+x^3 = (1+x)(a+x^2)}
\\\\
$
\text{Example: }
$\\$
a=2 \qquad 2+2x+x^2+x^3 = (1+x)(2+x^2) \\
a=1 \qquad 1+1x+x^2+x^3 = (1+x)(1+x^2)
$
}$$

heureka  Dec 5, 2014
 #1
avatar
+5

You have to play around with it a bit (or a lot) using trial-and-error trying different possibilities until it works.

 

Check your answer here: http://m.wolframalpha.com/input/?i=factorize+x%5E3%2Bx%5E2%2B2x%2B2&x=0&y=0

 

Guest Dec 5, 2014
 #2
avatar+20549 
+5
Best Answer

x^3+x^2+2x+2 factor by grouping so it ends up with two binomials.

$$\small{
\text{Formula:}
$
\boxed{a+ax+x^2+x^3 = (1+x)(a+x^2)}
\\\\
$
\text{Example: }
$\\$
a=2 \qquad 2+2x+x^2+x^3 = (1+x)(2+x^2) \\
a=1 \qquad 1+1x+x^2+x^3 = (1+x)(1+x^2)
$
}$$

heureka  Dec 5, 2014
 #3
avatar+94087 
0

This factorization could be handy to remember.  Thanks Heureka.

Melody  Dec 5, 2014

34 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.